The computer system in the context of the application of Artificial Intelligence - Stancu, Adriana Iuliana (Acta Universitatis Danubius. Juridica, 2024)
The Council of Europe adopted Recommendation R(89)9 on computer crime and published a report containing a minimum list and an optional list of computer crimes. If the member states will take into account these models in the elaboration of national laws, a European harmonization will be achieved regarding computer crime, with special regard to computer fraud. Artificial intelligence (hereinafter abbreviated AI) is the ability of a machine to imitate human behavior, being programmed to think and act like a human. One of the key features of AI is continuous learning, based on external stimuli and information gathered from the environment. AI observes the surrounding reality and acts accordingly, without the need for human help or assistance. Of essence is the fact that from the sphere of information technology that is of interest through their particularities.